Influence on the conversion of DMS to MSA and SO42− in the Southern Ocean, Antarctica. (15th July 2020) - Yan, Jinpei; Zhang, Miming; Jung, Jinyoung; Lin, Qi; Zhao, Shuhui; Xu, Suqing; Chen, Liqi
Abstract: Dimethyl sulfide (DMS), methanesulphonic acid (MSA) and sulfate (SO4 2− ) were measured simultaneously at high-time resolution in the Southern Ocean (SO) during February and March 2018, to characterize the conversion of DMS to MSA and SO4 2− in the marine atmosphere. DMS concentrations ranged up to ~10890.5 ng m −3 (with an average of 899.8 ± 957.9 ng m −3, representing the standard deviation), which were much higher than the MSA concentrations (with an average of 30.6 ± 16.8 ng m −3 ) and SO4 2− concentration (148.1 ± 32.5 ng m −3 ) in the aerosol phase. The spatial distribution of MSA was different from the distribution of DMS. The ratio of MSA to DMS (RM ) ranged up to ~ 0.31, with an average of 0.044 ± 0.045. RM value decreased dramatically as DMS concentration increased, when DMS concentration was below 1000 ng m −3 . The effects of temperature and relative humidity (RH) on RM were mostly negligible, indicating that neither DMS concentration, nor RH and temperature was the key parameter for the conversion of DMS to MSA in the SO. Ratios of nss-SO4 2- to DMS (RS ) were used to estimate the conversion of DMS to SO4 2− . The calculated RS with mean Rp (the ratio of MSA to nss-SO4 2- ) value correlated well with the observed RS, which provided an useful method to estimate the biogenic SO4 2− from the oxidation of DMS in the marine atmosphere, as biogenic SO4 2− levels can be calculated with Rs and DMS concentrations. The estimated biogenic SO4 2− levels ranged up to 163.8 ng m −3, with an average of 47.1 ± 30.2 ng m −3 in the SO during the cruise. The results extend the knowledge of the conversion of DMS to MSA and SO4 2− in the marine atmosphere. Graphical abstract: Image 1 Highlights: Air DMS, MSA and SO4 2− were measured with high-time-resolution in the Southern Ocean. MSA and SO4 2− concentrations were not associated with air MSA levels. The conversion rates of DMS to MSA were very low even in high air DMS levels. The DMS level was much higher than its conversion products in the Southern Ocean.